Totally laparoscopic treatment of vaginal cuff dehiscence: A case report and systematic literature review. (2016) - Thomopoulos, T.; Zufferey, G.
Highlights: Minimal invasive approaches to hysterectomy, such as total laparoscopic or robotic, can lead to higher incidence of vaginal cuff dehiscence. Vaginal evisceration is a rare but life-threatening complication if it is misdiagnosed. Even if several approaches for the management of the vaginal herniation have been describe in the literature, the entirely laparoscopic treatment seems to be safe and effective, demanding nevertheless a high surgical experience. Abstract: Introduction: To highlight the laparoscopic management as a feasible treatment option for vaginal cuff dehiscence with intestinal evisceration after hysterectomy. Presentation of case: We report a rare case of a 49-year-old postmenopausal woman who was admitted to the emergency department with vaginal herniation of approximately 40 cm of small bowel 3 months after total laparoscopic hysterectomy, treated laparoscopically exclusively. Discussion: The patient underwent a laparoscopic reduction of the protruded mass, inspection of the entire small bowel and closure of the vaginal dehiscence. She was discharged home in a good health and the postoperative course remains uneventful 6 months later. Our systematic review of the literature found 116 cases of vaginal evisceration, which were described as early as 1864. There is no consensus on the ideal method of surgical repair. To our knowledge, only 2% (3 cases) were treated totally laparoscopically and 10% by a combined approach (laparoscopic and vaginal). Although the current evidence does not suggest that one approach is preferred to the others, the laparoscopic approach seems to be the new trend for the management of this surgical emergency. Conclusion: Totally laparoscopic repair in experience hands seems to be a safe approach to cure vaginal evisceration after pelvic surgery.